2019
DOI: 10.1103/physreve.100.062207
|View full text |Cite
|
Sign up to set email alerts
|

Chaotic advection and mixing by a pair of microrotors in a circular domain

Abstract: In this work we study chaotic mixing induced by point micro-rotors in a bounded two dimensional Stokes flow. The dynamics of the pair of rotors, modeled as rotlets, are non Hamiltonian in the bounded domain and produce chaotic advection of fluid tracers in subsets of the domain. A complete parametric investigation of the fluid mixing as a function of the initial locations of the rotlets is performed based on pseudo phase portraits. The mixing of fluid tracers as a function of relative positions of micro-rotors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…On the one hand, the appearance of Poisson structure in the active Cosserat crystal may be expected, since it can be shown that any odd-dimensional linear system yields a Poisson structure [45]. On the other hand, many previous examples of non-linear symplectic structure arising in the field of active matter share a common feature, namely the identification of orientation variables as conjugate momenta to displacements [26][27][28][29][30][31][32][33][34]. We suspect a similar structure is present in previous works involving two-body problems and that additional Lie symmetries could be found, reducing the dynamical space to a single conjugate pair.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, the appearance of Poisson structure in the active Cosserat crystal may be expected, since it can be shown that any odd-dimensional linear system yields a Poisson structure [45]. On the other hand, many previous examples of non-linear symplectic structure arising in the field of active matter share a common feature, namely the identification of orientation variables as conjugate momenta to displacements [26][27][28][29][30][31][32][33][34]. We suspect a similar structure is present in previous works involving two-body problems and that additional Lie symmetries could be found, reducing the dynamical space to a single conjugate pair.…”
Section: Discussionmentioning
confidence: 99%
“…While this form of Hamilton's equations is not symmetric under time reversal, reflecting the presence of irreversible forces and torques, the nonequilibrium potential implied by the Hamiltonian admits a conceptual simplification of the stability criteria derived directly from the linear equations of motion. We conclude with a discussion on how the long-ranged stability of the active Cosserat crystal differs from that of the active Cosserat medium and how this approach may be generally useful in overdamped active particle mechanics [26][27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Viscosity generally prevents turbulence from occurring in microfluidic devices, which prevents efficient mixing. Microrotors can generate strong vortices, which are an important component of efficient mixing, and thus effectively promotes the mixing of substances in the solution, making them effectively microscopic “stir bars” . Furthermore, the interactions among the individual microrotors can lead synergistically to collective phenomena such as active turbulence, making the mixing induced by the ensemble greater than the sum of that of the individual rotors.…”
Section: Applications Of Microrotorsmentioning
confidence: 99%